Academic Burnout pada Generasi Alpha di Era Metaverse - Syifa Andini Fathyadiva (Universitas Mathla'ul Anwar Banten, 2026)
The rapid development of digital technology in the metaverse era has significantly influenced the learning patterns, social interactions, and psychological conditions of Generation Alpha. As a generation that grows up in a highly digital environment, Generation Alpha is increasingly exposed to gadgets, online learning platforms, social media, digital games, and virtual spaces. Although digital technology provides various opportunities for learning, creativity, and access to information, excessive and uncontrolled use may increase the risk of academic burnout. This study aims to analyze the factors contributing to academic burnout among Generation Alpha in the metaverse era. This research employed a library research design using a systematic literature review approach. Data were obtained from scientific articles indexed in Google Scholar through Publish or Perish. The search used the keywords “academic burnout,” “burnout akademik,” “Generation Alpha,” “Generasi Alpha,” “metaverse era,” “era metaverse,” “digital technology,” and “smartphone addiction,” with the publication years limited to 2023–2025 for the main articles analyzed. From 17 initially identified articles, 5 articles met the inclusion and exclusion criteria and were analyzed using content analysis and thematic synthesis. The findings show that academic burnout among Generation Alpha in the metaverse era is mainly influenced by excessive use of digital technology, digital fatigue, academic pressure, low self-control, lack of parental supervision, and insufficient social-emotional support from families and schools. These findings indicate that preventing academic burnout requires collaboration among parents, teachers, schools, and school counselors through digital literacy, character education, balanced digital learning, and early detection of academic burnout symptoms.